FORECASTING OF AIRCRAFT USING THE METHODS OF FORESIGHT: FOREIGN EXPERIENCE - N. P. Velikanova; O. I. Karasev; A. A. Polozov-Yablonsky (Научный вестник МГТУ ГА, 2016)
In the article the forecasts of the aircraft industry made within the framework of international foresight studies of the last decade are discussed. The objectives, scope, topics and level of detail of these projects are defined. Comparative analysis of foresight studies of the EU, Canada, France, USA, Australia, Japan, Korea, India and Russia allows to create a collective "Image of the Future" of the global aircraft industry, reflecting the wide range of customers needs and expectations.In the twenty-first century foresight became an instrument of public policy building in developed countries. The foresight studies for aviation sector demonstrate noticeable differences: some of them are dedicated to the prospects of aircraft industry as a whole, others are studying special issues such as aviation safety. Most part of modern foresight projects consider the aviation prospects within the context of global challenges, environmental, energy and technological trends (development of new materials, intelligent technology, etc).Technologies considered by leading foresight projects are grouped into 10 thematic areas: aircraft design; aircraft engines; new materials, methods of their creation and development; avionics; information and communication technologies; ecology and environment protection; energy saving; ground operations (including operation of airports); aviation security; air traffic management. Despite the existing differences of sectoral goal-setting, some sustainable priorities were found. Among them there are three technological groups: technologies improving ecological performance and reducing harmful emissions; development of new materials and coatings for the aviation industry; the improvement of aviation safety.The performed analysis of aviation foresight results has shown the importance of strengthening international cooperation in the area of ecology, in particular the harmonization of environment protection requirements, of multidisciplinary approach to forecasting; orientation to the concept of "Grand Challenges", which provides for the transition from separate technology areas support to the search of complex solutions of the problems facing the world community.